2009
DOI: 10.1002/nml.238
|View full text |Cite
|
Sign up to set email alerts
|

The social processes of interorganizational collaboration and conflict in nonprofit organizations

Abstract: This article takes a qualitative approach to research in advanc-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 32 publications
(24 reference statements)
2
80
0
Order By: Relevance
“…Hudson et al (1999) supported the existence of this tension through encouraging collaborative parties to recognise where interdependence is appropriate and respect where independence is warranted. Tsasis (2009) also proposed that a balance between autonomy and dependence is required for effective collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Hudson et al (1999) supported the existence of this tension through encouraging collaborative parties to recognise where interdependence is appropriate and respect where independence is warranted. Tsasis (2009) also proposed that a balance between autonomy and dependence is required for effective collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Trust is built up gradually, through long-term commitment, further increasing collaborative effectiveness (Percy 2010). Tsasis (2009) found that partner organisations that did not have a clear and consistent direction were experienced as untrustworthy. This is because a relationship that had started as complementary could change into becoming competitive.…”
Section: Barriers In the Interpersonal Domainmentioning
confidence: 98%
“…A growing body of research suggests a potential dark side to nonprofit collaboration (Brinkerhoff and Brinkerhoff 2002;Galaskiewicz and Colman 2006;Gazley and Brudney 2007;La Piana and Hayes 2005;Schwartz 2001;Vangen and Huxham 2005), but most of this work focuses on the costs of collaboration as they impact individual organizations-their management (Selden et al 2006;Thomson and Perry 2006), their objectives (Eikenberry and Kluver 2004;Schwartz 2001), their viability (Guo and Acar 2005), their culture (Tsasis 2009), and the various characteristics of collaboration across sector lines (Park 2008;Gazley 2008;Guo 2007;Shaw 2003;Gazley and Brudney 2007). In contrast, we question the impact of an increasingly collaborative environment on the broader achievement of social objectives in society.…”
Section: Introductionmentioning
confidence: 98%